Exploring Traditional Nepalese Building Techniques and Timber’s Role Structural Integrity - Maharjan, Bipin; Singh Dongol, Moon (KEC Journal of Science and Engineering, 2024)
This paper aims to explore traditional Nepalese building construction techniques and the significant role of timber in enhancing the structural integrity and longevity of these buildings. With a long history of utilizing materials that are readily available locally, particularly wood, clay, stone, Nepal a country renowned for its rich architectural legacy has built buildings employing these resources. The study delves into the various traditional building techniques employed in Nepal, including the intricate craftsmanship and cultural significance associated with them. Additionally, it investigates the unique properties of timber that make it an ideal choice for construction in the Nepalese context. The finding talks about the construction of buildings various techniques which are employed to assemble structures. This includes information, on building materials, functional space allocation and the terminologies used in building construction. These terminologies hold value as they are derived from our tradition, in building construction technology. The findings of this research can serve as a valuable resource for architects, engineers, conservationists, and policymakers involved in the restoration and sustainable development of traditional Nepalese buildings.